Pengaruh Influencer Marketing dan Brand image terhadap Keputusan Pembelian Produk Wardah di Tangerang Selatan - Lapania Konita (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
Nowadays, many brands, be it in the field of beauty or others, utilize influencer marketing as one of the promotional strategies to market their products. Moreover, now that everyone has social media, it is easier to launch marketing strategies through influencer marketing. Brand image also has an important role in improving purchasing decisions, with a strong brand image consumers will not hesitate to buy and even make repeat purchases. This study aims to identify the impact of influencer marketing and brand image on Wardah's purchasing decisions in South Tangerang. The research method used is a quantitative approach involving 55 respondents, and distributing questionnaires using Google Forms. Respondents taken are individuals who have used Wardah products at least once. The data used consisted of primary data. The analysis technique applied is Partial Least Squares (PLS), by conducting validity, reliability, and hypothesis testing. The results showed that both influencer marketing and brand image have a significant (positive) impact on purchasing decisions.